Association of cardiorespiratory fitness with risk of adverse cardiovascular outcomes in cancer patients: a cohort study - Wang, Yutong; Song, Xinyang; Xu, Tao; Chen, Yanwen; Guo, Ying; Wang, Fang (Frontiers in Cardiovascular Medicine, 2025)
BackgroundCardiorespiratory fitness (CRF) has gained attention for its potential association with cardiovascular risks. This study aims to examine the association between CRF and adverse cardiovascular outcomes [atrial fibrillation (AF), heart failure (HF), cancer therapy-related cardiovascular toxicity (CTR-CVT)] in cancer patients and explore whether enhancing CRF could improve these outcomes.MethodsThe association between three key exposure factors of CRF—resting heart rate (RHR), maximum heart rate (HRmax), and maximal oxygen uptake (V̇O2max)—and the risk of adverse cardiovascular outcomes were assessed using Cox regression analysis.ResultsRHR is significantly associated with an increased risk of adverse events (HF: HR = 1.013, 95% CI 1.008–1.019, P < 0.001; CTR_CVT: HR = 1.006, 95% CI 1.004–1.008, P < 0.001), except for AF (HR = 0.998, 95% CI 0.994–1.001, P = 0.194). HRmax was associated with a lower risk of CTR_CVT events (HR = 0.995, 95% CI 0.993–0.998, P < 0.001), but this was not the case for HF and AF (HF: HR = 1.000, 95% CI 0.992–1.009, P = 0.962; AF: HR = 0.998, 95% CI 0.992–1.003, P = 0.420). V̇O2max was negatively correlated with all adverse events, with HRs ranging from 0.957 to 0.958 (P < 0.05 for all). RHR showed a significant non-linear relationship with CTR_CVT (Pnon-linear < 0.0001), AF (Pnon-linear < 0.0001), and HF (Pnon-linear = 0.0057). Similarly, V̇O2max demonstrated a notable non-linear relationship with CTR_CVT (Pnon-linear = 0.0081) and AF (Pnon-linear = 0.0093). No non-linear relationship between HRmax and the outcomes was observed.ConclusionCardiorespiratory fitness, as measured by V̇O2max, is consistently negatively correlated with all adverse cardiovascular outcomes, suggesting that higher fitness levels are protective. These findings highlight the potential role of CRF in predicting cardiovascular risks in cancer patients, underscoring the importance of monitoring and improving physical fitness to mitigate adverse outcomes.